Unraveling the wrongful conviction : a guide for analyzing innocence claims - Grothaus, Daniel J. (Routledge, 2026)
"This book lays out the author's proven approach to investigating and assessing a defendant's claim of innocence whether pre-trial, or post-conviction. The author weaves his 35 years of experience into a simple step-by-step process, showing the reader how to objectively investigate a wrongful conviction. He uses his case histories to describe an alternative to the "trial and error" methods so often used. As a result, this book offers a methodical and repeatable approach to assessing and investigating a defendant's claim of innocence. The book refers to the actual investigations, which led to dozens of exonerations, prison releases, acquittals, and dismissed charges in Murder I cases. Claims of innocence may be common, but knowledge of an objective way to assess those claims is hardly universal. This book was written for the classroom and the field. It is essential reading for the student, the Innocence Project volunteer, practitioner or anyone interested in correcting a wrongful conviction, or avoiding the next false conviction"-- Provided by publisher.
Keywords: Judicial error.; Murder -- Investigation.; Presumption of innocence.; False imprisonment -- Law and legislation.; Writ of error coram nobis.; Criminal justice, Administration of.; elektronické knihy; electronic books